Кар’єра та гендер - Ходирєв, Є. О. (ХНУРЕ, 2020)
After graduating many students facethe problem with realizing their potential due to reasons that are not dependent on them.It’s important to make sure that people with equal skills and abilities have equal opportunities in their lifeand the success of their career does not depend on their gender.
Keywords: філософія; гендер